Dynamics of inflammatory factors expression in ischemic brain tissue injury - Tonko Marinović; Silvio Bašić; Dominik Romić; Branimir Nevajda; Lovorka Đerek; Jurica Maraković; Marina Raguž (MDPI AG, 2019)
Ischemic stroke is one of the most common cause of mortality and disability in the modern world. Still, therapeutic options remains modest. Aim of the study was to present dynamics of inflammatory factors expression (C reactive protein, procalcitonin, interleukin 10) in patients after ischemic stroke. Our study included 101 patients divided in thrombolised and non-thrombolised groups. Inflammatory factors concentration in serum was determinate at admission, 24, 48 hours and seven days after the initial onset, while neurological assessment was measured at the admission, 24 hours, seven days and three months after the initial onset using National Institute of Health Stroke Scale and Rankin Scale. Certain pattern was observed in dynamics of inflammatory factors: intensive increase in first and second day after the stroke, followed by decrease till day seven in both groups. Additionally, thrombolised group showed significant neurological improvement. Although well investigated, the role of inflammatory factors in the ischemic stroke still stays controversial. High association of C reactive protein and interleukin 10 values suggest potential prognostic role in patients follow-up, while the role of procalcitonin values still remains unclear.